Virginio Rognoni’s lesson (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
Virginio Rognoni passed away in his sleep in his beloved home in Pavia last September. These pages are dedicated to his memory. They retrace his extraordinary biography, made up of political, legal, and civil engagement, and they also recall the many occasions when Rognoni honoured the Faculty of Political Science of the University of Milan with his presence. Brief excerpts of his teachings are reproduced here. They represent a precious legacy for those who were lucky enough to listen to them and a reason for deep gratitude on our part.
Keywords: memory, terrorism, mafia, teachings, democracy, civil culture